Analisis Pengaruh Kualitas Pelayanan terhadap Kepuasan Anggota Koperasi Simpan Pinjam - Nurlelasari Ginting; Imelda Barus (STKIP PGRI SITUBONDO, 2022)
The existence of environmental changes that occurred and people’s behavior to keep their money in the bank. It is encourage the increased demand for banking services usage needs. The increasing of competition in the banking industry created a variety of ways to attract customers. This study aims to determine how the customer response to the quality of services provided by credit union to its customers. This research is a quantitative descriptive, this study population is the customer data in 2012 at credit union with total 2500 people, samples in this study amounted to 100 respondents drawn using Slovin formula and sampling technique in this study is probability sampling with simple random sampling. The findings of the study on dimensions which are tangible, reliability, responsiveness, assurance and empathy will help the community to determine the quality of service credit union . In the responsiveness dimension, reliability, assurance, empathy and tangible researchers found positive results or good result, but there are several factors that are still rated poorly by customers of credit union unit.